1998
DOI: 10.1002/(sici)1097-4547(19981101)54:3<390::aid-jnr10>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Receptor‐activated Ca 2+ increases in vibrodissociated cortical astrocytes: A nonenzymatic method for acute isolation of astrocytes

Abstract: A new nonenzymatic method for the acute isolation of astrocytes from rat cerebral cortex is described. A vibratory device was used to dissociate the cells from thin brain slices, and the method yielded fresh and relatively well-preserved astrocytes without previous enzyme incubation. These cells were examined in a microspectrofluorometric system for measurement of changes in intracellular free calcium concentrations ([Ca2+]i), and their expression of various neurotransmitter receptors was determined. Acutely i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…We detected a 25% increase in intracellular Ca 2ϩ concentration induced by quinpirole, a D2-receptor-specific agonist (Fig. 6 a and b waves on activation, analogous to other neurotransmitter receptors (21,23,26). Therefore, it is possible that D2-facilitated Ca 2ϩ excitation in astrocytes may increase neuronal excitability (19)(20)(21)(22)(23)(24) and, ultimately, synaptic transmission (25), whereas neuronal D2 recep- Fig.…”
Section: Discussionmentioning
confidence: 95%
“…We detected a 25% increase in intracellular Ca 2ϩ concentration induced by quinpirole, a D2-receptor-specific agonist (Fig. 6 a and b waves on activation, analogous to other neurotransmitter receptors (21,23,26). Therefore, it is possible that D2-facilitated Ca 2ϩ excitation in astrocytes may increase neuronal excitability (19)(20)(21)(22)(23)(24) and, ultimately, synaptic transmission (25), whereas neuronal D2 recep- Fig.…”
Section: Discussionmentioning
confidence: 95%
“…It is noteworthy that in both cases, morphine failed to influence the cAMP response of glial cultures, demonstrating the lack of functional classic opioid receptors (Eriksson et al, 1990). Opioidinduced calcium signaling within astrocytes was subsequently found to respond broadly to several Hansson et al, 2008), Hansson et al, 2008), and ␦ ( Thorlin et al, 1998b) opioid receptor agonists in a selective classic opioid receptor in an antagonist sensitive fashion.…”
Section: Initiation Of Non-neuronal Cell Intracellular Signaling In Tmentioning
confidence: 97%
“…Immature astrocytes display significantly greater (Gurwell et al, 1996;Tryoen-Toth et al, 1998) and ␦ (Thorlin et al, 1998b) opioid receptor expression. Persson et al (2000) demonstrated that astrocyte ␦ opioid receptor protein levels increased 2-fold during mitosis and mRNA increased 3-fold during the G 1 /S transition.…”
Section: Central Anatomical Locations Of Opioid Analgesic Action and mentioning
confidence: 99%
“…Furthermore, adrenergic and glutamatergic interactions can also greatly affect both cAMP-and calcium-related signaling in astroglial cells (15). Both ␣ 1 -AdRs (3,16) and mGluRs (I) (17)(18)(19) are expressed on astrocytes and stimulate phospholipase C (PLC) to hydrolyze phosphoinositides. The nature of astrocytic mGluRs is still somewhat unclear.…”
mentioning
confidence: 99%